Effects of moisture absorption analysis of kevlar/carbon/glass/polyurethane epoxy hybrid sandwich composites with nano silicon particles - Mani, Megavannan; Thiyagu, M; Krishnan, Pradeep Kumar (Advances in materials and processing technologies (Abingdon, England), 2025)
Hybrid sandwich polymer composites are widely used in aviation applications due to their attractive properties, such as their excellent strength capability, high modulus values, excellent stiffness properties, and greater wear resistance. This study aims to analyse the mechanical properties of degraded hybrid sandwich specimens exposed to moisture and investigate the moisture behaviour of the degraded sandwich panels. These panels are reinforced with woven fabrics made of kevlar, carbon, and glass fibres. The hand layup technique was employed to create the structures. The hybrid sandwich composite samples are submerged in normal seawater at ambient temperature for varied duration's to measure the fibres' water absorption characteristics. The study investigated the mechanical characteristics of an ageing moisture hybrid sample during tensile, flexural, and compressive tests. Novel stacking sequence arrangements (0 1 K /0 1 C /0 1 G /PUR/0 1 G /0 1 C /0 1 K ) were used to enhance the stiffness, load-carrying capacity, yield strength, and other mechanical characteristics of the sandwich structures. The degraded sandwich panels demonstrated that water absorption significantly influences the tensile, flexural, and compressive properties of degraded sandwich structures compared with the results of regular sandwich panels. The tensile (31.67%, 40.40%, and 47.089%), flexural (63.13%, 66.05%, and 70.14%), compressive (33.14%, 39.37%, and 38.40%), and water absorption (3.75%, 3.97%, and 4.71%) test results were analysed.